Efecto de la posición de la semilla de tacaco [Sechium tacaco (Pittier) C. Jeffrey], Sobre la germinación (ING) - Campos Castillo, Rónald (1992)
The effect of seed position on germination using sterilized sand as substrate under room temperature conditions (mean = 20°C, max.= 24,2°C, min. = 16,2°C) was evaluated in tacaco [Sechium tacaco (Pittier) C. Jeffrey]. The treatments were: A= seed placed horizontally on substrate, B= seed buried horizontally in substrate, C=seed halfburied in lateral position, D= seed halfburied in vertical position, distal extreme up, E= seed halfburied in vertical position, distal extreme down. After 28 days, the treatments with higher germination percentages (not statistically different) were E, B and C, with germination percentages of 84,6; 82,7 and 73,1; respectively. None germination was observed for treatments A and D, but treatment D was the most detrimental, since 82,7% of seeds were deteriorated compared with 32% in treatment A.